Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2014
DOI: 10.1145/2632048.2632054
|View full text |Cite
|
Sign up to set email alerts
|

StudentLife

Abstract: Much of the stress and strain of student life remains hidden. The StudentLife continuous sensing app assesses the day-today and week-by-week impact of workload on stress, sleep, activity, mood, sociability, mental well-being and academic performance of a single class of 48 students across a 10 week term at Dartmouth College using Android phones. Results from the StudentLife study show a number of significant correlations between the automatic objective sensor data from smartphones and mental health and educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
211
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(218 citation statements)
references
References 35 publications
6
211
1
Order By: Relevance
“…Despite these challenges there is also growing interest in research on social interaction, such as the StudentLife project of Wang et al [222] that uses ubiquitous smartphone sensors to collect information to help improve the health and mental wellbeing of college students. Other work is exploring how interfaces can be designed to support group interaction, for example by recognizing and adapting to group configurations known as 'F-formations' [133,134].…”
Section: Social and Collaborative Experiencesmentioning
confidence: 99%
“…Despite these challenges there is also growing interest in research on social interaction, such as the StudentLife project of Wang et al [222] that uses ubiquitous smartphone sensors to collect information to help improve the health and mental wellbeing of college students. Other work is exploring how interfaces can be designed to support group interaction, for example by recognizing and adapting to group configurations known as 'F-formations' [133,134].…”
Section: Social and Collaborative Experiencesmentioning
confidence: 99%
“…In their study that involved 12 patients over a period of 12 weeks, they have shown that mobile behavioral sensing system could identify both depression and mania states with an accuracy of more than 70% and detect state-change with very high precision and recall [10] . The StudentLife project pioneered the use of mobile behavioral sensing technology for monitoring the daily behavior of college students to assess the impact of academic workload on the students' mental states [11]. In their 10-week study on a class of 48 Computer Science students, they found that social activities such as person-to-person conversations and sleep duration were important indicators of students' mental states.…”
Section: Related Workmentioning
confidence: 99%
“…Importantly, embedded smartphone sensors (e.g., accelerometers, light sensors, GPS) are now advanced enough to allow for passive and continuous data collection [6,7], which are increasingly being used to enhance understanding of the relationship between objective behavior and mental health status [7][8][9][10][11][12][13]. For example, Saeb and colleagues [8,14] provided preliminary evidence that extracting location-based mobility features could be used to detect depression level.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Saeb and colleagues [8,14] provided preliminary evidence that extracting location-based mobility features could be used to detect depression level. However, virtually all studies leveraging passive data in the context of mental health has focused on depression or general mood [7,9,15,16]. While some studies have attempted to use other forms of passive data in the context of social anxiety [17], none have investigated the feasibility of using mobility features to detect social anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation